New species and new distributional record of the genus Broscosoma Rosenhauer, 1846 (Coleoptera, Carabidae, Broscinae) from China - Jiang, Ri-Xin; Liu, Xiao-Fan; Wang, Shuo (Zootaxa, 2021)
Two new species of the genus Broscosoma Rosenhauer, 1846 are described from China: Broscosoma guoliangi sp. nov. from Fujian Province and Broscosoma qiului sp. nov. from Chongqing City, respectively. In addition, Broscosoma ribbei rougeriei Deuve & Tian, 2002 is newly recorded from Derung-Nu Autonomous County Gongshan, Yunnan Province, China.